Sexuality among street children in light of HIV and aids in Blantyre and Lilongwe urban - Banda, Chancy (Kamuzu University of Health Sciences, 2022)
Street children/youth are at risk of HIV infection and other STIs in Malawi. To develop effective prevention strategies, adequate information on STIs and HIV/AIDS as well as the services provided in light of HIV and AIDS is urgently required to this vulnerable population. In this paper, data from structured interviews will be collected to build a picture on street children's knowledge on STIs and HIV/AIDS and determine their accessibility and utilization of available STIs and HIV/AIDS preventive, curative and rehabilitative services in light of HIV/AIDS in Malawi. A non-experimental qualitative design using a structured interview guide will be used to obtain information from the participants. Data will be obtained from 30 respondents from two settings, thus Lilongwe and Blantyre urban streets through Tikondane Children's Centre and Chisomo Children's Club respectively. The findings will be analysed manually using content analysis and then presented in a qualitative form.